1999
DOI: 10.1046/j.1440-1614.1999.00609.x
|View full text |Cite
|
Sign up to set email alerts
|

The Senior Psychiatrist Survey III: attitudes towards personal ageing, life experiences and psychiatric practice

Abstract: The effects of life experiences on psychiatrists' attitudes towards personal ageing are complex. Attitudes towards personal ageing have little impact on psychiatric practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Although not reaching statistical significance, RAQ score means were lower for generalist psychologists than for specialists, with higher scores corresponding to more positive attitudes to personal aging (Table 3). This is within the range of means obtained in the Senior Psychiatrist Survey of Draper et al (1999). Cronbach's alpha for the RAQ was .87.…”
Section: Raq Analysissupporting
confidence: 78%
See 1 more Smart Citation
“…Although not reaching statistical significance, RAQ score means were lower for generalist psychologists than for specialists, with higher scores corresponding to more positive attitudes to personal aging (Table 3). This is within the range of means obtained in the Senior Psychiatrist Survey of Draper et al (1999). Cronbach's alpha for the RAQ was .87.…”
Section: Raq Analysissupporting
confidence: 78%
“…A questionnaire (Reactions to Ageing Questionnaire; RAQ) has been recently developed for this purpose with a recent validation study (Gething, 1994;Gething et al, 2002), suggesting misconceptions and ageism existing among British and Australian nurses. It has also been utilised in the Royal Australian and New Zealand College of Psychiatrists Senior Psychiatrist Survey (Draper, Gething, Fethney, & Winfield, 1999) with positive attitudes towards personal ageing being linked to age, gender and self-rated good health. A large-scale survey examining predictors of negative attitudes towards older adults using the RAQ carried out by the Lincoln Gerontology Centre at La Trobe University in Victoria found a lack of education in gerontology as a significant factor (Wells, Foreman, Gething, & Petralia, 2004).…”
mentioning
confidence: 99%
“…Gender issues were more frequently mentioned, particularly by females. This will be further explored in Part III of this trilogy [3].…”
Section: Discussionmentioning
confidence: 99%
“…Draper and colleagues 9 surveyed Fellows of the Royal Australian and New Zealand College of Psychiatrists on their attitudes to personal ageing. They were interested in perceived benefits and drawbacks of age on psychiatric practice, and concluded that attitudes towards personal ageing have little impact on psychiatric practice, but that this is a complex area.…”
Section: Older Psychiatrists In Practice: Relationships With Patientsmentioning
confidence: 99%